The effect of 6-week core stability training on core endurance and physical performance in professional rugby players: A randomized controlled pilot study - Chamila S. Senavirathna; Anuja P. Mallawaarachchi; Aranjan L. Karunanayake; Sampath Gunawardena (Asian Journal of Medical Sciences, 2021)
Background: Core stability training (CST) is used to enhance sports performance. The relationship between core endurance and physical performance in rugby players had not been evaluated before in Asia.